2020
DOI: 10.13181/mji.oa.204223
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among health care workers in a tertiary hospital in Southern Nigeria: knowledge, attitude, and practices

Abstract: BACKGROUND Self-medication is linked to the inappropriate and irrational use of medicines. This study aimed to determine the knowledge, attitude, and practice of self-medication among health care workers (HCWs) in a tertiary hospital in Southern Nigeria. METHODS In a cross-sectional study carried out between June 2018 and December 2018 at Irrua Specialist Teaching Hospital, Edo State, 206 consenting HCWs were interviewed using validated questionnaires on their knowledge (assessed as good, fair, and poor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…HCPs older than 44 years were 2.7 times more likely to practice self-medication than those below 44 years. This finding differs from some previous reports that showed that young people were more likely to use self-medication [ 1 , 14 ]. The older age group is more vulnerable to COVID-19 with subsequent adverse outcomes than the younger age group [ 32 34 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…HCPs older than 44 years were 2.7 times more likely to practice self-medication than those below 44 years. This finding differs from some previous reports that showed that young people were more likely to use self-medication [ 1 , 14 ]. The older age group is more vulnerable to COVID-19 with subsequent adverse outcomes than the younger age group [ 32 34 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The nature of their training empowers them to recognize and hopefully seek treatment earlier than the uninformed individual. While this may be beneficial in most instances, it may also adversely affect their health as HCPs have poor health-seeking abilities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in several studies from Iran, Ethiopia, India and Nigeria involving self-medication among pharmacy or medical students, the source of the medicines used in self-medication were OTC medicines from medical stores or pharmacies [5][6][7][8]. Even healthcare workers from a study in Nigeria prefer self-medicating with OTC [9]. In a different study in India involving patients from a dental hospital, all participants bought their self-medication from medical stores or pharmacies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many published studies reported that most health workers have a positive attitude towards self-medication. 42,49,50,51 In fact, instead of overemphasizing the activities that try to address the BHS's perception towards responsible selfmedication, the Myanmar technical working groups may require to advocate the BHS for following the national treatment guidelines and drug policy and to promote their comprehensive knowledge about drug safety, quality, and rational usage.…”
Section: Discussionmentioning
confidence: 99%